KEJENUHAN, MENGASIHI DIRI, DAN GENDER DAPATKAH MEMPENGARUHI BELAJAR MANDIRI SISWA DI MASA PANDEMI COVID 19? - Dwi Nur Rachmah; Rahmiyati Rahmiyati (Jurnal Visi Ilmu Pendidikan, 2022)
This study aims to find out what factors can affect students' independent learning during the covid 19 pandemic. As is known, the covid 19 pandemic has changed the learning process from conventional to online learning. This ultimately requires students to be able to learn more independently, which means students understand more problems, search for literature and solve problems independently. State Boredome, self Compassion and gender are thought to affect self directed learning students. This study uses a quantitative approach with a sample of 198 students on SMA IT in South Kalimantan. Research data was collected through google form using self directed learning scale, sstate boredome scale and self compassion scale. Data analysis using multiple regression with the results that there are effect of state boredom, self compassion and gender on self directed learning students. However, of the three research variables, it was only self compassion which significantly affected self directed learning students.